2006
DOI: 10.1111/j.1476-4431.2006.00189.x
|View full text |Cite
|
Sign up to set email alerts
|

Historical and physical parameters as predictors of severe hyperkalemia in male cats with urethral obstruction

Abstract: Objective: To evaluate selected historical and physical parameters as predictors of hyperkalemia in male cats with urethral obstruction. Design: Retrospective study. Setting: Veterinary teaching hospital. Animals: Two hundred and twenty-three male cats. Interventions: None. Measurements and main results: The metabolic derangements of 223 male cats that presented with urethral obstruction from 1997 through 1999 were reported in a companion article. Approximately 12% of the cats had multiple, life-threatening me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 5 publications
0
8
1
2
Order By: Relevance
“…Patients with severe hypothermia (rectal temperature < 35.6°C), bradycardia (heart rate < 120 beats/min), signs of depression, or severe hyperkalemia (serum potassium concentration > 8 mmol/L) or acidemia (venous pH < 7.1) would typically be at a high risk of death without emergency intervention and intensive care and so were excluded. Physical examination parameters used to screen cats for inclusion in the study were selected on the basis of their ability to predict the presence of severe hyperkalemia, 4 and none of the cats that were considered qualified for inclusion on the basis of physical examination findings had to be excluded later on the basis of serum potassium concentration or venous pH. The severity of azotemia at the time of initial examination was not used as an exclusion criterion because accumulation of uremic toxins, although deleterious, is not immediately life threatening.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with severe hypothermia (rectal temperature < 35.6°C), bradycardia (heart rate < 120 beats/min), signs of depression, or severe hyperkalemia (serum potassium concentration > 8 mmol/L) or acidemia (venous pH < 7.1) would typically be at a high risk of death without emergency intervention and intensive care and so were excluded. Physical examination parameters used to screen cats for inclusion in the study were selected on the basis of their ability to predict the presence of severe hyperkalemia, 4 and none of the cats that were considered qualified for inclusion on the basis of physical examination findings had to be excluded later on the basis of serum potassium concentration or venous pH. The severity of azotemia at the time of initial examination was not used as an exclusion criterion because accumulation of uremic toxins, although deleterious, is not immediately life threatening.…”
Section: Discussionmentioning
confidence: 99%
“…Feline urethral obstruction is a life‐threatening condition and one of the most common presentations in small animal emergency hospitals. Previous reports have described risk factors, frequency, treatment, and management strategies of feline lower urinary tract disease . Initial medical therapy for urethral obstruction involves IV fluid therapy, a deobstruction procedure involving the passage of a urinary catheter, maintenance of an indwelling urinary catheter, and hospitalization for postobstructive diuresis, and correction of electrolyte derangements and azotemia if present .…”
Section: Introductionmentioning
confidence: 99%
“…These findings contradict those of a previous study that reported that cats with previous obstruction tended to be less metabolically compromised than cats experiencing their first obstruction event. 5 It is difficult to explain why cats with multiple urethral obstruction episodes of may be more likely to experience bladder hemorrhage, except to speculate that cats with repeat events have previous injury to the bladder wall, predisposing them to hemorrhage. This hypothesis may be supported by the 1 patient in this study that had a necropsy performed.…”
Section: Discussionmentioning
confidence: 99%
“…Feline urethral obstruction is common and can be life‐threatening without rapid treatment. Etiologies, risk factors, clinical characteristics, and treatment recommendations have been described previously . While the prognosis for urethral obstruction is generally good, mortality can vary, and ranged from 5.8% to 8.9% in several studies (including cases that died or were euthanized).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation